IMPLEMENTATION OF PSAK 107 IN SHARIA ACCOUNTING FOR GOLD RAHN PAWN PRODUCTS AT PEGADAIAN SYARIAH IN KENDARI - Muhamad Tonasa; Nurul Imamah; Rawdatul Amanah; Alpiana (Academic Bright Collaboration, 2025)
This study aims to examine the implementation of PSAK 107 in gold rahn products at the Islamic pawnshop, Kendari Branch, focusing on assessing sharia accounting compliance, financial reporting transparency, and alignment with DSN–MUI Fatwa No. 26/DSN-MUI/III/2002. This research adopts a qualitative approach by integrating in-depth interviews, participatory observation, and documentation analysis of financial reports and operational practices within the pawnshop institution. The study finds that the recognition and measurement of rahn receivables and ijarah income comply with PSAK 107. However, disclosure remains limited due to centralized reporting. Differences in staff understanding and minor inconsistencies with DSN–MUI Fatwa No. 26/DSN-MUI/III/2002 indicate the need for better alignment and internalization of sharia principles. This study is limited to a single branch, which may restrict the generalizability of findings. Nevertheless, it provides important implications for improving human resource capacity, enhancing localized reporting mechanisms, and strengthening the alignment between accounting standards and sharia fatwas to improve transparency and accountability. This research contributes to the limited empirical literature on the implementation of PSAK 107 in rahn practices, particularly at the branch level, and highlights critical gaps between regulatory frameworks and operational realities in Islamic pawnshop institutions.